Marine Radar Target Ship Echo Generation Algorithm and Simulation Based on Radar Cross-Section - Chang Li; Xiao Yang; Hongxiang Ren; Shihao Li; Xiaoyu Feng (Journal of Marine Science and Engineering)
In this study, a simplified radar echo signal model suitable for radar simulators and a Radar Cross-Section (RCS) calculation model based on the Physical Optics (PO) method was developed. A comprehensive radar target ship echo generation algorithm was designed, and the omnidirectional radar RCS values of three typical ships were calculated. The simulation generates radar target ship echo images under varying incident angles (0–360°), detection distances (0–24 nautical miles), and three common target material properties. The simulation results, compared with those from existing radar simulators and real radar systems, show that the method proposed in this study, based on RCS values, generates highly realistic radar target ship echoes. It accurately simulates radar echoes under different target ship headings, distances, and material influences, fully meeting the technical requirements of the STCW international convention for radar simulators.